METHODS OF INVENTORY TURNOVER MANAGEMENT AT CAR SERVICE ENTERPRISE BASED ON STATISTICAL TIME-SERIES ANALYSIS - S. E. Stepina; T. P. Agureyeva; A. E. Stepina (Russian Journal of Economics and Law)
The article views the possibility of increasing the efficiency of service enterprises functioning, which form the tertiary sector of economy. The authors propose one of the modern approaches aimed at providing the efficient functioning of enterprises, including the service ones, that is, the logistic support of the processes by inventory turnover management.